Elementary School Teachers’ Competence Development in Dealing with The COVID-19 Conditions: An Interpretative Phenomenological Study - Sirajuddin Islam; Endang Sri Indrawati (Faculty of Psychology, Diponegoro University, 2022)
The Covid-19 pandemic has had an impact on the education system, leading to school closures and switching toonline learning with very short notice. In order to support the effectiveness of online learning, it is necessary todevelop teachers’ competence in the utilization and use of online media. The study aimed to investigate educators’teaching experience during online learning during the Covid-19 pandemic. The three teachers who participated inthis study were recruited from the Gubeng 1 Public Elementary School in Surabaya. Interview transcripts wereanalyzed qualitatively by using an interpretative phenomenological analysis approach. Data analysis raises threemain themes: 1) an overview of online learning implementation in elementary schools, 2) challenges in the teachercompetence development process, 3) support for teacher competence development. The results of this studyindicate the importance of developing teacher digital competence to increase the effectiveness of online learning.Support from related parties is also needed to encourage the success of online learning.